2016
DOI: 10.1007/s10964-016-0513-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yoga for Preventing Adolescent Substance Use Risk Factors in a Middle School Setting: A Preliminary Group-Randomized Controlled Trial

Abstract: Adolescence is a key developmental period for preventing substance use initiation, however prevention programs solely providing educational information about the dangers of substance use rarely change adolescent substance use behaviors. Recent research suggests that mind–body practices such as yoga may have beneficial effects on several substance use risk factors, and that these practices may serve as promising interventions for preventing adolescent substance use. The primary aim of the present study was to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 104 publications
1
102
1
12
Order By: Relevance
“…Four studies did not provide gender data ( 31 , 33 – 35 ), five studies included only females ( 36 40 ) and six studies only males ( 41 – 46 ). Moreover, the target population of two studies was adolescence ( 47 , 48 ) and of seven studies were young adults or college students ( 32 , 34 , 42 , 44 , 49 51 ). One trial ( 52 ) was focused on individuals with mild intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies did not provide gender data ( 31 , 33 – 35 ), five studies included only females ( 36 40 ) and six studies only males ( 41 – 46 ). Moreover, the target population of two studies was adolescence ( 47 , 48 ) and of seven studies were young adults or college students ( 32 , 34 , 42 , 44 , 49 51 ). One trial ( 52 ) was focused on individuals with mild intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, most students in the present study reported that yoga had beneficial effects on stress and mood, a finding that is similar to quantitative studies that measured psychosocial outcomes via self-report questionnaires (e.g., Felver et al, 2015; Frank et al, 2014; Noggle, Steiner, Minami, & Khalsa, 2012). However the present study is also unique in that it provided an opportunity to examine potential similarities and differences between the current qualitative findings and the results of the larger quantitative study within which the current study was embedded (Butzer, LoRusso et al, 2016). The quantitative study found that students in the control condition reported a greater willingness to smoke cigarettes immediately post-intervention than students in the yoga condition, however immediate pre- to post-intervention effects did not emerge for any of the other outcome measures such as mood impairment or perceived stress.…”
Section: Discussionmentioning
confidence: 97%
“…First, to our knowledge this is the first qualitative study of school-based yoga for 7 th grade students. In addition, the current study provides valuable information above and beyond the data gathered via self-report questionnaires in the larger quantitative study (Butzer, LoRusso et al, 2016). For example, the qualitative interview questions regarding the intervention solicited student experiences on detailed aspects of the intervention such as relative preference for individual components.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations